2020
DOI: 10.1016/j.heliyon.2020.e04764
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 lockdown and its impact on tropospheric NO2 concentrations over India using satellite-based data

Abstract: The World Health Organization has declared the COVID-19 pandemic a global public health emergency. Many countries of the world, including India, closed their borders and imposed a nationwide lockdown. In India, the lockdown was declared on March 24 for 21 days (March 25-April 14, 2020) and was later extended until May 3, 2020. During the lockdown, all major anthropogenic activities, which contribute to atmospheric pollution (such as industries, vehicles, and businesses), were restricted. The current study exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 51 publications
6
46
0
1
Order By: Relevance
“…5 ). Our spatio-temporal findings about declined tropospheric NO 2 concentrations is well corroborate with other studies where the average short-term reductions were reported <12% post-lockdown in India ( Biswal et al, 2020 ; Naqvi et al, 2020 ).
Figure 5 The average tropospheric NO 2 concentration variations in the study area during a one-month pre- and post-lockdown period.
…”
Section: Resultssupporting
confidence: 92%
“…5 ). Our spatio-temporal findings about declined tropospheric NO 2 concentrations is well corroborate with other studies where the average short-term reductions were reported <12% post-lockdown in India ( Biswal et al, 2020 ; Naqvi et al, 2020 ).
Figure 5 The average tropospheric NO 2 concentration variations in the study area during a one-month pre- and post-lockdown period.
…”
Section: Resultssupporting
confidence: 92%
“…During the lockdown period, this work and other recent studies highlighted the impact of restricted anthropogenic activities on air quality across India and other parts of the world (Sharma et al 2020;Jain and Sharma 2020;Mahato et al 2020;Dantas et al 2020;Chauhan and Singh 2020;Mor et al 2020). In India, particulate matter (PM 2.5 and PM 10 ) and NO 2 show a significant reduction of up to 40-50% in the many megacities during the lockdown period as highlighted by Jain and Sharma (2020), Mahato et al (2020), Singh et al (2020a), and Biswal et al (2020). The air quality index (AQI) improved by 15-44% in India's different parts (Sharma et al 2020).…”
Section: Air Quality In Lockdown and Implication For Better Air Qualitysupporting
confidence: 51%
“…The satellite-based studies by Biswal et al (2020) and Pathakoti et al (2020) estimated the change in NO2 levels using OMI observations whereas Siddiqui et al (2020) utilised TROPOMI to compute the change over eight major urban centres of India. Biswal et al (2020) reported that average OMI NO2 over India decreased by 12.7 %, 13.7 %, 15.9 %, and 6.1 % during the subsequent weeks of the lockdown. Similarly, Pathakoti et al (2020) reported a decrease of 17 % in average OMI NO2 over India as compared to the pre-lockdown period and a decrease of 18 % against the previous 5-year average.…”
Section: Introductionmentioning
confidence: 99%